Modelling of Cost Estimates for the Geometrical Calibration of Upright Oil Storage Tanks - Agboola, Olayinka Oluwole; Akinnuli, Olufemi Basil; Akintunde, Aremu Mutalubi; Kareem, Buliaminu (International Journal of Energy Economics and Policy, 2019)
Cost estimation is a fundamental activity in engineering management and business decision making. It normally involves estimating the quantity of labor, materials, utilities, floor space, sales, overhead, time and other parameters over a given period of time. These estimates are used typically as inputs to deterministic analysis methods or to stochastic analysis methods. Cost of tank calibration which depends on the factors such as the capacity of tank, number of labour, method adopted, equipment etc. has not been standardized. In an attempt to standardize the cost of tank calibration, two separate models, one each for the two common methods of tank calibration; Manual Strapping Method (MSM) and Electro Optical Distance Ranging (EODR). These models were validated with actual cost of tank calibration obtained from four renowned calibration companies in the country and were found to be within the acceptable limit of ±10% deviation. Keywords: calibration, modeling, cost estimation, oil storage tank, standardization JEL Classifications: C2, C3, C5, D7 DOI: https://doi.org/10.32479/ijeep.8271